Ungkapan Penolakan dalam Bahasa Bugis pada Interaksi Masyarakat Desa Mangelorang Kabupaten Maros - Muhammad Adam Rifandi; Andi Agussalim Aj; Asia M. (Indonesian Journal of Social and Educational Studies, 2022)
This study aims to: (1) describe the form of expression of rejection of the Bugis language in the interaction of the Mangeloreng village community, Maros Regency. (2) describe the strategy of expressing the rejection of the Bugis language in the interaction of the Mangeloreng village community, Maros Regency The research design is descriptive qualitative. The data in this study are in the form of words, as well as sentences which contains rejection in the interaction of the people of Maros district. Technique data collection is tapping, recording, and recording, namely by listening community conversations in daily interactions with the language Bugis then dialysis which includes the form of expressions of rejection and strategy rejection expression. Based on the results of research and data analysis found forms and strategies rejection expression. (1) The form of the expression of direct rejection and the form of indirect expression of rejection using commands and sentences news. (2) The strategies for expressing rejection found in the research are, the strategy of expressing rejection using suggestions, the strategy of expressing rejection with time delays, reasons, and strategies for expressing rejection with apology.Keywords: Expression Of Rejection, Form, Strategy.